Francisco Delicado, Retrato de la Loçana andaluza - Lillian von der Walde Moheno (Medievalia)
Francisco Delicado, Retrato de la Loçana andaluza, ed. de Tatiana Bubnova, Doral, FL: Stockcero, 2008, XI-XLIX + 221 pp.